2014
DOI: 10.1039/c3cc47944g
|View full text |Cite
|
Sign up to set email alerts
|

The luminescence properties of linear vs. kinked aurophilic 1-D chains of bis(dithiocarbamato)gold(i) dimers

Abstract: Widely varying luminescence spectra are reported for 1-D chains of bis(dithiocarbamato)gold(I) dimers. Variable pressure luminescence spectra elucidate the effect of angular overlap on the emission properties of the aurophilic chain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
28
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 20 publications
4
28
0
Order By: Relevance
“…The X‐ray diffraction measurement of Au(diethyldithiocarbamate) crystal revealed that it existed as a polymer consisting of dimeric units ([Au 2 (C 4 H 10 NCS 2 ) 2 ] n · x CH 2 Cl 2 ) as reported previously . Based on this measurement and earlier investigations,, it is suggested that the gold(I)‐dithiocarbamates would exist in the form of polymers having the formula, [Au 2 (diethyldithiocarbamate) 2 ] n with gold:dithiocarbamate ratio of 1:1. The central Au I atom in 3 adopts a nearly linear arrangement and the neighboring units are associated to each other through gold‐gold interactions.…”
Section: Resultssupporting
confidence: 74%
“…The X‐ray diffraction measurement of Au(diethyldithiocarbamate) crystal revealed that it existed as a polymer consisting of dimeric units ([Au 2 (C 4 H 10 NCS 2 ) 2 ] n · x CH 2 Cl 2 ) as reported previously . Based on this measurement and earlier investigations,, it is suggested that the gold(I)‐dithiocarbamates would exist in the form of polymers having the formula, [Au 2 (diethyldithiocarbamate) 2 ] n with gold:dithiocarbamate ratio of 1:1. The central Au I atom in 3 adopts a nearly linear arrangement and the neighboring units are associated to each other through gold‐gold interactions.…”
Section: Resultssupporting
confidence: 74%
“…The nature of the lowest-energy excited state can thus be ascribed to a LL′CT state, formed upon a transfer of electronic density from the dithiocarbamate ligand to the triphenylphosphine moiety. This is in stark contrast to the electronic structure in the presence of aurophilic interactions, where the frontier orbitals have strong M-M character [4,5]. The calculated HOMO-LUMO gap at the PBE1PBE/Lanl2dz level of theory in the gas phase is 32100 cm −1 (312 nm), suggesting a high-lying first excited state.…”
Section: Frontier Orbitalsmentioning
confidence: 49%
“…Dithiocarbamate (dtc) complexes are attractive due to their simple structures and wide variation of luminescence properties [3][4][5]. In this note we describe a monometallic gold(I) compound with Au-dtc coordination, an example of a molecular structure without Au(I)-Au(I) interactions.…”
Section: Introductionmentioning
confidence: 99%
“…Over time, aurophilic interactions, which have comparable strength to a hydrogen bond, start to form which could account for the solubility issues and precipitation from solution. The stacking of discrete dimeric units in the solid-state is not new in gold dithiocarbamate chemistry [28,[31][32][33][34][35]. yield.…”
Section: Resultsmentioning
confidence: 99%